Current Issues in the Diagnosis and Treatment of Endometrial Carcinoma - Stubert, J.; Gerber, B. (Geburtshilfe und Frauenheilkunde, 2016)
Endometrial carcinoma is the most common carcinoma of the female genital tract. Its most important clinical sign is postmenopausal bleeding. An endometrial biopsy is essential for diagnosis. Treatment decisions are governed by tumour risk assessment and patient comorbidity, which is often present. Pelvic and paraaortic lymph node dissection is unnecessary in low risk cases (definition: pT1 a, G1/2) and adjuvant radiotherapy and systemic treatments are usually avoidable. Treatment of high-risk patients (G3 and/or pT1b) and palliative cases is difficult and not well standardised. New molecular-based subtype classification may help treatment decision making in future.
Keywords: endometrial carcinoma; paraaortic lymph node dissection; endometrial thickness; ultrasound; postmenopausal bleeding